G20 in Buenos Aires : End of US-China Trade War? - Lee, Su-Hyun (2018)
The 2018 G20 Summit in Buenos Aires, concluded amidst rising tensions between the US and China over trade. The G20 leaders’ final declaration this year addressed important issues like digitalisation, infrastructure, food security, and migration, besides some concessions to the US in trade.